Finite Element Analysis as a Method to Study Molluscan Shell Mechanics. Issue 3 (18th December 2017) - Lemanis, Robert; Zlotnikov, Igor
Abstract : The clade Mollusca is a highly diverse and disparate group of terrestrial and aquatic invertebrates, the taxon containing over 100 000 known species including some of the most intelligent invertebrate animals. Their shells are exemplar systems in the study of biomechanics, biomineralization, and biomimetics. Research into understanding the superior biomechanical properties of the shell and how these properties relate to the animals ecology have required a diverse range of methods at multiple length scales; one particularly powerful method is finite element analysis. Finite element analysis is a robust engineering method that has a long‐standing history in biomechanical research. This review summarizes the application of finite element analysis in the study of both the mechanical properties of different molluscan shell ultrastructures as well as macro‐scale modeling of the shell. From the calculation of elastic constants to the origins of the strength of nacre and the relationship between shell folding and ecology, this article provides a window into how finite element analysis can further our understanding of mechanics and functional morphology. Abstract : Decades of research have gone into the study of the molluscan shell using a variety of methods. Here, the authors review how one particular method, finite element analysis, has been used to further our understanding of the mechanical properties and functional morphology of the shell at both the ultrastructural and macro‐structural levels.